THE CONTRIBUTION OF ABU YUSUF'S THOUGHT: ISLAMIC ECONOMIC LAW RENEWAL IN THE PUBLIC FINANCE - Rahmaeni Nur (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri Bone, 2020)
This paper will specifically examine the economic legal thought of Abu Yusuf, especially in terms of Islamic public financial management. This problem is raised because it is based on the need for a reference in managing a country's finances so that a balance of economic fundamentals can occur. Management of public finances such as tax sometimes becomes a difficult problem to solve. Especially in Indonesia, what often appears is sometimes taxpayersmanipulate tax reports plus extortion from certain parties that provide guarantees to be free from legal cases. The data source in this study is the book of al-kharaj by Abu Yusuf as primary data. The style of study used is adab al mashlahah al-mu'tabarah wa al-'iqtishâd. Contextualizing the current economic reality. The findings in this study indicate that the economic thinking of Abu Yusuf prioritizes the concept of the benefit of the Ummah. The management of public finances, both concerning revenue and expenditure, the government must think about the benefit of the people. Financial management by promoting justice and balance. The implication of the findings of this study is that the management of state finances must be based on the benefit of the citizens. The indicator of all State money management is the welfare of the people. So the government in every program, must think and prioritize the benefit.Keywords: Renewal; Abu Yusuf, Public Finance.